On Solvability for Some Classes of System of Non-Linear Integral Equations in Two Dimensions via Measure of Non-Compactness - Rakesh Kumar; Shubham Kumar; Mohammad Sajid; Bhupander Singh (Axioms, 2022)
In this paper, we present some results of coupled fixed points for the system of non-linear integral equations in Banach space. Our results enlarge the results of newer papers. Additionally, we prove the applicability of those results to the solvability of the system of non-linear integral equations. Finally, we give an example to validate the applicability of our results.